Developing ethnomathematics-based interactive digital book to improve mathematical connections and self-confidence: The PMRI approach - Ratna Marlina; Wahyu Hidayat; Tatang Supriatna (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
One reason students have difficulty understanding the relationships among quadrilaterals, area, and perimeter is the lack of innovative teaching materials in schools. Therefore, this study aims to develop an interactive digital book using a valid, practical, and effective PMRI approach based on ethnomathematics to improve students' mathematical connection skills and self-confidence. The research method employed was Design Research of the development study type. The research subjects consisted of three subject matter experts, three language experts, and one media expert, as well as 64 students from an Islamic middle school in West Bandung, Indonesia. The students included three eighth-grade students for one-to-one testing, nine eighth-grade students for small-group testing, and 52 seventh-grade students for field testing. The research instruments included validation sheets for subject matter, media, and language experts; unstructured interviews; student response questionnaires; a self-confidence questionnaire consisting of 40 The results of the study indicate that the mean validation score from subject matter experts was 95% (highly valid), from language experts 98% (highly valid), and from media experts 95% (highly valid). Student responses reached 92% (highly practical). The post-test significance values for mathematical connection skills (0.000) and self-confidence (0.001) were both below 0.05, indicating that the developed digital book was effective in improving students’ mathematical connection skills and self-confidence compared to conventional learning. Additionally, students’ self-confidence was categorized as high.